Model analysis of private teachers' innovative work behavior improvement after the COVID-19 pandemic - Lie, Darwin; Romy, Elly; Sudirman, Acai (Journal of Education and Learning (EduLearn), 2024)
After the COVID-19 pandemic, educational organizations' learning process experienced significant changes, especially related to innovative work behavior. It is undeniable that building innovative work behavior requires strong self-efficacy and organizational commitment and is supported by conducive workplace happiness. This research aims to analyze models for improving the innovative work behavior of private teachers after the COVID-19 pandemic based on self-efficacy, organizational commitment, and workplace happiness. The research model is oriented towards a quantitative causality approach. Data was collected online using a Google form, and a sample of 100 teachers was obtained. Using a purposive sampling formula, the foundation for sample determination is geared toward a non-probability sampling strategy. Instrument tests, normality tests, regression tests, correlation tests, hypothesis tests, and coefficient of determination were all utilized in data analysis. The results of the study demonstrate that innovative work behavior is highly influenced by workplace happiness, organizational commitment, and self-efficacy. According to the study's conclusions, encouraging creative work behavior requires teachers to have the confidence to do so. Furthermore, the psychological state of educators has a significant impact on their ability to generate novel and creative ideas.